Nalar Fikih Kebangsaan K.H. Afifuddin Muhajir: Islam, Pancasila dan Keindonesiaan - Mutho’am, Mutho’am; Bashori, Akmal (SALAM: Jurnal Sosial dan Budaya Syar-i, 2023)
Indonesia is not an Islamic country, but Indonesia is also not anti-Islamic. Pancasila positions monotheism in its first principle in line with Islamic theology. Likewise, in the Constitution, it is stated